Impact of service quality on customer satisfaction towards increasing payment collection/ Halimatul Saadiah Abdul Razak - Abdul Razak, Halimatul Saadiah (Faculty of Business and Management, 2010)
The purpose of the study was to measure the impact of service quality provided on payment collection towards customer satisfaction in Tenaga Nasional Berhad (TNB), Jalan Yahya Awal, Johor Bahru especially towards domestic customer. In this study it will help the organization to improve and increase their sales. The issue of payment collection is significantly importance as it is the source of financing for development purposes. The payment collection levied to pay the cost of services provided such as electricity utility, and cover the maintenances cost. The payment generally levied according to the electric capacity use and it different according to the type of electric equipment that they use and time duration that take in using the equipment for every each domestics’ customers. Capacity usage might increase if users use the electricity wastefully which lead to the increasing of electric. Therefore this study only focuses on the domestic customer which is residential building owner. Analysis of survey responses based on 250 respondents from Johor Bahru area found that most of the variables investigated in the study significantly contributed towards impact of service quality on customer satisfaction towards increasing payment collection. In this research, research using several types of analysis which are reliability analysis, frequency analysis, descriptive analysis and correlation analysis. From the research and analysis researcher found that some improvements have to be taken by the organization especially on their service quality. Organization have to take seriously towards empathy, because from the research researcher found that most of the customer not satisfied with the organization empathy. TNB might have a lot of customer, to focus individualize for each customer might not be easy. Customers come to the organization, bagging for installment, and create a lot of reason to avoid from payment. It is difficult for the organization to be more empathy because it will hard for the organization to achieve goals which is profitability. Therefore some improvement needs to be taken in that area. Secondly researcher found that, organization also lack focus on reliability quality to the customer. Reliability is the ability to perform the promised service dependably and accurately. Most of the customer responds that the organization lacks in focusing on reliability, because of the large number of TNB customer, to be reliable to all of them might difficult. In this case, organization has to find way in order to cope with this problem. Service quality is very important therefore organization have to fulfill as the promises. Organization should provide a proper awareness programs and take certain actions to the customer in other to increase payment collection.